Strategic Talent Management in Gen Z Remote Work Settings: What Really Drives Performance? - Helmy Ivan Taruna; Sonny Fransisco Siboro; Yulianto Yulianto; Ulfa Rahma Dhini; M. Mahdi Alatas (Lembaga Pengembangan Kinerja Dosen, 2026)
This study examines how strategic talent management shapes the performance of Generation Z employees, particularly those born between 1997 and 2007 and actively working within Indonesia’s expanding digital economy. While this cohort is often described as highly adaptive and technologically fluent, many organizations still rely on conventional HR practices that do not fully align with the realities of remote and hybrid work. Using a quantitative approach, the study applies Structural Equation Modeling with Partial Least Squares (SEM-PLS) to survey data from 200 professionals recruited via LinkedIn. The results point to Talent Deployment (β = 0.349) and Talent Development (β = 0.247) as the strongest predictors of Workforce Agility, which in turn significantly drives Organizational Performance (R² = 0.277). What stands out, though, is not just the strength of these relationships, but how they connect. The mediation analysis suggests that talent strategies only become effective when they activate adaptive behaviors. Without agility, the impact weakens. This leads to a broader conclusion that performance is less about static talent inputs and more about how fluidly those inputs are mobilized. The study proposes a Human Capability Architecture perspective, emphasizing flexible role alignment and continuous upskilling as practical priorities for firms navigating an increasingly volatile digital environment.